2000
DOI: 10.1055/s-2000-8874
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Biomarkers Increase During Exercise-Induced Vasodilation in the Forearm

Abstract: The purpose of the study was to determine if exercise-induced vasodilation was associated with an increase in forearm plasma levels of nitric oxide (NO) biomarkers (NO2- + NO3- and L-citrulline). Twelve healthy subjects (27+/-6 yrs) performed incremental rhythmic forearm exercise with the nondominant hand for 6 min each at 15, 30 and 45% of maximal voluntary contraction (MVC). Forearm blood flow (FBF) was determined in the exercise arm using venous occlusion plethysmography. Blood samples were obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is likely that the HI resistance exercise protocol is capable of promoting greater blood mobilization (Copeland et al, 1996) and, consequently, higher amounts of postexercise muscle oxygen in relation to LI training. Consistent with this idea, it is speculated that the HI protocol may have stimulated the increased production of nitric oxide, a known potent vasodilator, because it mobilized a larger volume of blood (Brown et al, 2000). Thus, lower oxygen percentages were observed in the LI and LI+BFR protocols, suggesting that exercise intensity is an important factor influencing the acute responses of oxygen saturation.…”
Section: Discussionmentioning
confidence: 82%
“…It is likely that the HI resistance exercise protocol is capable of promoting greater blood mobilization (Copeland et al, 1996) and, consequently, higher amounts of postexercise muscle oxygen in relation to LI training. Consistent with this idea, it is speculated that the HI protocol may have stimulated the increased production of nitric oxide, a known potent vasodilator, because it mobilized a larger volume of blood (Brown et al, 2000). Thus, lower oxygen percentages were observed in the LI and LI+BFR protocols, suggesting that exercise intensity is an important factor influencing the acute responses of oxygen saturation.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, moderate exercise (60% of peak workload) increased oxidative stress in patients suffering from cystic fibrosis but not in healthy volunteers [59]. In conclusion, despite inconsistencies in the literature, most research showed that moderate exercise has the potential to induce oxidative stress and increase total antioxidant status [25,53,[60][61][62].…”
Section: A Single Bout Of Moderate Exercise and Oxidative Stressmentioning
confidence: 90%
“…Nitric oxide (NO), a signaling molecule with a wide range of physiological functions, has been suggested to improve exercise performance by enhancing exercise-induced vasodilation [17], increasing the oxygenation status in the working muscles, and improving VO 2 kinetics [18]. Supplementations of arginine or citrulline, both of which are precursors to NO, have been suggested to improve performance in high-intensity exercise [19,20].…”
Section: Introductionmentioning
confidence: 99%